2016
DOI: 10.1111/1471-0307.12320
|View full text |Cite
|
Sign up to set email alerts
|

Surface coating of silver nanoparticles on polyethylene for fabrication of antimicrobial milk packaging films

Abstract: In this study, antimicrobial packaging films were prepared by coating silver (Ag) nanoparticles onto the surface of low density polyethylene (LDPE) films modified by corona air plasma. The possibility of these films for use in the packaging of milk was studied. The influence of input power of the corona discharge treatment on the surface modification and performance of the fabricated Ag/LDPE nanocomposite films was also investigated. The prepared antimicrobial packaging films showed promising antimicrobial eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This fact was confirmed when increasing the ethanol percentage up to 95%, where no migration was detected at all. Even in the worst case (50 µm film in contact with 3% acetic acid), the immobilization of silver into the polymeric matrix was very effective, since less than one-thousandth of the total content was transferred to the liquid simulant, in agreement with previous studies with similar materials and test conditions [40,41].…”
Section: Release Of Silver From Active Films By Icp-mssupporting
confidence: 88%
“…This fact was confirmed when increasing the ethanol percentage up to 95%, where no migration was detected at all. Even in the worst case (50 µm film in contact with 3% acetic acid), the immobilization of silver into the polymeric matrix was very effective, since less than one-thousandth of the total content was transferred to the liquid simulant, in agreement with previous studies with similar materials and test conditions [40,41].…”
Section: Release Of Silver From Active Films By Icp-mssupporting
confidence: 88%
“…Several works have shown that some inorganic nanomaterials, such as metallic NPs, and nanostructured synthetic polymers are useful for preventing spoilage and pathogenic microbiota associated with dairy products like cheese and fluid milk when used as preservatives for direct mixture with the product or as nanocomposites in the packaging [ 31 , 32 , 33 ]. In this regard, nanocomposite films with better characteristics for food packaging can be produced from metal and other inorganic NPs, for example, titanium oxide, silver, zinc oxide, copper and gold.…”
Section: Nanostructures For Antimicrobial Deliverymentioning
confidence: 99%
“…Novel packaging systems, which include active and smart packaging, have been also introduced in milk packaging. It was demonstrated that antimicrobial active packaging films (prepared by coating silver nanoparticles on LDPE) can be efficient against microorganisms present in milk thus increasing its shelf life (Bandpey et al, 2016). With regards to food-package interaction it was observed that it is not only the fat content of the foodstuff, such as in dairy products, that influences the migration of lipophilic migrants from the packaging to the food item.…”
Section: Packaging Of Milkmentioning
confidence: 99%